2021
DOI: 10.3390/foods10051072
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Gochujang on Inflammation in a DSS-Induced Colitis Rat Model

Abstract: Gochujang is a traditional Korean fermented soy-based spicy paste made of meju (fermented soybean), red pepper powder, glutinous rice, and salt. This study investigated the anti-inflammatory effects of Gochujang containing salt in DSS-induced colitis. Sprague–Dawley (SD) rats were partitioned into five groups: normal control, DSS control, DSS + salt, DSS + mesalamine, and DSS + Gochujang groups. They were tested for 14 days. Gochujang improved the disease activity index (DAI), colon weight/length ratio, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…These results are consistent with the findings from Peran et al ( 2007 ) and Khodir et al ( 2019 ). Also, Mahoro et al ( 2021 ) found that; DSS-induced bloody diarrhoea, weight loss, shortening of the colon, and mucosal deterioration in a rat model of DSS-induced colitis. Otherwise, only amoxicillin–probiotics treatment could significantly ameliorate the body weight loss and the high stool score caused by DSS/LPS, while both treatments (amoxicillin and probiotics–amoxicillin) showed inhibitory effects on the high colon weight-to-length ratio ( p < 0.01), as well as colon macroscopic lesion score ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the findings from Peran et al ( 2007 ) and Khodir et al ( 2019 ). Also, Mahoro et al ( 2021 ) found that; DSS-induced bloody diarrhoea, weight loss, shortening of the colon, and mucosal deterioration in a rat model of DSS-induced colitis. Otherwise, only amoxicillin–probiotics treatment could significantly ameliorate the body weight loss and the high stool score caused by DSS/LPS, while both treatments (amoxicillin and probiotics–amoxicillin) showed inhibitory effects on the high colon weight-to-length ratio ( p < 0.01), as well as colon macroscopic lesion score ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of S. sciuri, Desulfovibrio C21_c20, R. gnavus and Akkermansia muciniphila were significantly increased in the DSS group. S. sciuri was found in the colon tissues of patients with colitis and was reported as an oral bacterium that promoted intestinal inflammation in colitis [49] . Desulfovibrio subspecies are sulfate-reducing anaerobic Gram-negative bacteria associated with increased gut permeability [50] .…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Interestingly, the meju microbiota is influenced by various factors, including weather conditions, provinces, and manufacturers, altering the microbiota composition of Gochujang subsequently. 13,18,19 Although the general microbial composition of Gochujang and its health beneficial functions have been studied well, 14,[20][21][22][23] the dissimilar physiological effects of Gochujang based on its distinct microbial communities have not been fully investigated. Therefore, the aims of this study were: (1) to study the constipation ameliorative effects of two different types of Gochujangs in aspects of their microbial communities; (2) to investigate their underlying molecular mechanisms, and (3) to measure the distinct effects of two different types of Gochujangs on the gut microbiota composition.…”
Section: Introductionmentioning
confidence: 99%